ATSAR ISTIKHDAM THARIQAH AL-QIRA'AH AL-MUTAKARIRAH FI MAHARAH AL-KITABAH - Rihlah, Rihlah; Royani, Ahmad (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2016)
Repeated reading method is a technique used to improve students 'reading fluency at a beginning level popularized by Samuel in 1979. This study aimed to determine the student's ability to write dictation', and to know the use of repeated reading technique in aloud reading technique, as well as to reveal the effect of the use of repeated reading method on students' skills in writing dictation. The method of this study is an experimental method with the research design of pre-test post-test control group design. The sample of the research was 44 students, comprising 22 students for each the experimental and control classes. The data analysis of two groups used t-test. The results showed that there is an influence of the use of repeated reading method on students' skills in writing dictation. This is based on the result of ttest (2.64) and the result of ttable (2.02) at the 5% significance level. Thus, we concluded that the result of ttest is > ttabel.DOI : 10.15408/a.v3i1.2908